VD_FINDINFO Décision / 2012 / 690 vom 29. Juni 2012 - VD Tribunal cantonal (2012)
AVOCAT D'OFFICE, AVOCAT, PARTIE NON REPRÉSENTÉE | 135 al. 3 let. a CPP (CH), 395 let. b CPP (CH), 429 al. 1 let. a CPP (CH)